The two-component system BvrR/BvrS regulates the expression of the Type IV secretion system VirB in Brucella abortus - Martínez-Núñez, Carola (2010)
The pathogenesis of Brucella is related to the ability to multiply intracellularly, an event controlled by the two-component system BvrR/BvrS (TCS BvrRS) and the type IV secretion machinery VirB (T4SS VirB). We have hypothesized that the TCS BvrRS transcriptionally regulates the T4SS VirB. To test this hypothesis, we have compared the levels of VirB proteins in the wild-type strain Brucella abortus 2308 and mutant strains devoid of the sensor and regulator genes (bvrS and bvrR mutants, respectively). While the bvrR and bvrS mutants showed low levels of the VirB1, VirB5, VirB8, and VirB9 proteins, the same proteins were overexpressed in the bvrR mutant complemented with a plasmid carrying a functional bvrR gene. Quantitation of virB5 mRNA confirmed these data and indicated that the influence of the TCS BvrRS on the T4SS VirB occurs at the transcriptional level. The expression of the transcriptional activator VjbR also depended on the TCS BvrRS. In addition, we demonstrate a direct interaction between the promoter region of the VirB operon and the response regulator BvrR. Altogether these data demonstrate that the TCS BvrRS controls the expression of the T4SS VirB through direct and indirect mechanisms.